J Pancreat Cancer Treat 2019
DOI: 10.36959/829/398
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoid Carcinoma of the Pancreas: A Case Report

Abstract: Histological examination of resected specimens showed that tumor's proliferation adopted a hepatoid architecture, organized in large trabecular pattern, and composed of large polygonal cells with abundant eosinophilic cytoplasm, centrally located nuclei, nucleoli (Figure 3a). Immunohistochemical staining of tumor cells showed a focal positivity for CK19 and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…HC has a histological appearance of proliferating large tumor cells, with a trabecular pattern of large polygonal cells seen with abundant eosinophilic cytoplasm, central nuclei, and nucleoli [ 12 ]. A majority of PHC cases have elevated serum AFP levels, hence it can be used as a marker to determine the success of surgery or response to chemotherapy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HC has a histological appearance of proliferating large tumor cells, with a trabecular pattern of large polygonal cells seen with abundant eosinophilic cytoplasm, central nuclei, and nucleoli [ 12 ]. A majority of PHC cases have elevated serum AFP levels, hence it can be used as a marker to determine the success of surgery or response to chemotherapy [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on treatment protocol due to limited number of cases reported in the literature. Surgical resection is considered the preferred option [ 4 , 12 ]. Oral multitarget tyrosine kinase inhibitor, sorafenib, resulted in a 7-month progression-free survival, in a case of metastatic PHC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatoid carcinomas (HCs) are a group of heterogeneous tumors that represent the morphology and immunohistochemistry of focal hepatocellular carcinoma (HCC), which comprises of pure forms of HC or a combination of other morphological features of acinar cell carcinomas, endocrine tumors or ductal adenocarcinomas. It has been reported in different primary sites of various cell origins, including the stomach, esophagus, lungs, gallbladder, urinary bladder, colon, ampulla of Vater, uterus, fallopian tubes, adrenal gland, ovaries, thymus, biliary tract, and other sites (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Since Hruban et al (17) first reported primary pancreatic hepatoid carcinoma (PHC) in 1987, only 41 cases of primary PHC have been reported in the English literature, at least to the best of our knowledge (4,.…”
Section: Introductionmentioning
confidence: 99%